The Schwarz-Christoffel Conformal Mapping for “Polygons” with Infinitely Many Sides - Gonzalo Riera; Hernán Carrasco; Rubén Preiss (International Journal of Mathematics and Mathematical Sciences)
The classical Schwarz-Christoffel formula gives conformal mappings of the upper half-plane onto domains whose boundaries consist of a finite number of line segments. In this paper, we explore extensions to boundary curves which in one sense or another are made up of infinitely many line segments, with specific attention to the “infinite staircase” and to the Koch snowflake, for both of which we develop explicit formulas for the mapping function and explain how one can use standard mathematical software to generate corresponding graphics. We also discuss a number of open questions suggested by these considerations, some of which are related to differentials on hyperelliptic surfaces of infinite genus.